Glen Summit Paper - The Fuel-Supply of the United States. [Presidential Address at Glen Summit] - John Birkinbine (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1892)
Four meetings of the Institute have been held in the anthracite coal-fields of Pennsylvania, and excursioris into the district, in connection with meetings elsewhere, have familiarized our members with